The Influence of Local Government Expenditures for Education and and Education Levels on Poverty Levels in Aceh Province - Indah Mukthadila (MediaTrend, 2022)
This study intends to assess the impact of government spending and education onpoverty alleviation. Panel data is used from 2015 to 2019 in 23 districts/cities inAceh Province to analyze the impact of government spending on education and the number of graduates in poverty alleviation. The results of the study show that high school/vocational high school graduates and undergraduates contribute significantly to poverty alleviation. This study reveals that government spending on education and graduates at the elementary, junior high, diploma, and master/doctoral levels does not have a direct impact on poverty reduction. This study recommends that the Provincial Government of Aceh provide various alternative secondary education services in accordance with the educational model needed to obtain good human resources in terms of education. In addition, it is hoped that the realization of spending on education can improve or increase access and facilities in areas that still lack facilities and teaching staff so that all Indonesian people get an equal education. Then, the government must start programs such as entrepreneurship training so that graduates are able to open new business opportunities which are ultimately expected to be able to improve the living standards of the people of Aceh Province and get out of the cycle of poverty.